Gender and Game Genres Differences in Playing Online Games - Hassan, Haslina; Mailok, Ramlah; Hashim, Mashitoh (Journal of ICT in Education, 2019)
Online games are currently popular among teenagers as a way to entertain their time and having fun. Some claimed that by playing games could enhance learning ability, improved focus and attention, treat depression, less anti-social and many more. However, playing games could also become an addiction where some might involve with physical and health problems. This paper investigated gender-based students’ perceptions on playing games with their daily life. The perceptions study was developed based on ten items that related to students’ daily task. This study is also to identify the most popular game genres and genre-gender based preference from twelve game genres listed in this study. The data were collected among 116 students from Diploma in game design and development course offered by Faculty of Arts, Computing & Creative Industry at Sultan Idris Education University (UPSI), Malaysia. The results showed that majority of the students perceived themselves as love to play games however percentage of male students are higher than female students. The mean analyses also showed the highest score from ten (10) tasks is ‘meet new friends’ and this also the highest mean for both genders. The result also showed that ‘Adventure’ game genre is the most popular game genre among both gender while ‘music/dance’ genre is the least popular genre for male but the third popular game genre for female.